Pengaruh Literasi Keuangan dan Fear of Missing Out (FoMO) terhadap Gaya Hidup Konsumtif - Muhamad Radit; Indra Andriyana; M. Azka Irawan; Sri Mulyeni (Jurnal Manajemen Kreatif dan Inovasi, 2026)
The massive penetration of social media and e-commerce has fundamentally transformed the shopping habits of society, particularly among university students and Generation Z. Relentless promotional bombardments, coupled with the accessibility of "buy now, pay later" payment features, have made them increasingly prone to impulsive buying without careful consideration. Furthermore, the immense psychological urge to maintain a social presence and the (Fomo) make consumptive behavior in the digital space increasingly difficult to control. This study aims to investigate the development of this consumptive lifestyle in the modern era through a qualitative approach. A literature review design was applied, relying on relevant scientific journals and academic theses. The results of the analysis clearly indicate that Fomo drives individuals to prioritize emotional impulses for social validation over the actual utility of the purchased goods. While financial literacy has proven to act as a natural constraint against wasteful spending, theoretical financial knowledge often collapses under the weight of peer pressure and the allure of instant digital credit. In conclusion, the younger generation requires more than merely theoretical financial understanding; they need emotional discipline and the ability to filter social media influences to avoid falling into the trap of future debt.